PENGARUH TERAPI AKTIVITAS TERHADAP ANSIETAS PADA LANSIA DI PANTI JOMPO TRESNA WERDHA ABDI DHARMA ASIH KOTA - Tinah (Poltekkes Kemenkes Medan, 2021)
Anxiety is one of the most common mental health problems in the elderly. The provision of appropriate and accurate psychopharmacology as well as nursing therapy is not enough, but must be followed up with selected therapy modalities regularly and continuously until the normal functioning of stable normative behavior or adaptive behavior, one of which is group activity therapy. To determine the effect of group activity therapy on the level of anxiety in the elderly. The design of this study is a quasi-experimental design with a pre-post test group design with a total sample of 44 people. The independent variable is group activity therapy (TAK) and the dependent variable is anxiety. The instruments used are questionnaire sheets and observation sheets. The statistical test used the Wilcoxon test with a significance value of = 0.05. The anxiety level of the majority of the elderly before TAK therapy was severe anxiety as much as 40.91% and after TAK therapy the majority of the elderly with mild anxiety level as much as 47.73%. There was a difference in anxiety before and after giving group activity therapy with a P value of 0.000 (P <0.05). Group activity therapy has an effect on reducing anxiety levels in the elderly.